2021
DOI: 10.3390/w13081108
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Evolution of Marine Industry Structure on the Green Total Factor Productivity of Marine Economy

Abstract: The 14th five-year plan emphasizes the importance of marine ecology and environmental protection, and the green concept is incorporated into the high-quality development system of the marine economy. This research used the data of 11 coastal provinces and cities in China from 2006 to 2016, based on the super-efficiency slack-based measure model and global Malmquist index model. The objective was to calculate the green total factor productivity (GTFP) of the marine economy, to study the impact of the evolution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…As China attaches great importance to marine development, many scholars undertook a quantitative analysis of marine economy in China. Wei et al (2021) used the superefficiency slack-based measure model and global Malmquist index model to research the impact of the evolution of the marine industrial structure on marine economic [10]. Wu and Li (2022) completed a detailed analysis of the spatiotemporal evolution and types of marine economy and provided a new strategy for measuring many aspects of marine economic resilience [11].…”
Section: The Development Of Marine Technology Innovationmentioning
confidence: 99%
“…As China attaches great importance to marine development, many scholars undertook a quantitative analysis of marine economy in China. Wei et al (2021) used the superefficiency slack-based measure model and global Malmquist index model to research the impact of the evolution of the marine industrial structure on marine economic [10]. Wu and Li (2022) completed a detailed analysis of the spatiotemporal evolution and types of marine economy and provided a new strategy for measuring many aspects of marine economic resilience [11].…”
Section: The Development Of Marine Technology Innovationmentioning
confidence: 99%
“…It has been demonstrated that indicators like GDP and FDI in national economic development, as well as factors such as the level of land-based economic development and marine industry structure, can all have a significant impact on the marine economic TFP growth (Wang et al, 2021;Wei et al, 2021). As a result, variables like the gross ocean product, total imports and exports as a percentage of GDP, the number of marine research topics, and the share of marine tertiary industry in the gross ocean product are included in the meta-regression model in this paper to examine their effects on TFP growth in the marine economy.…”
Section: Economic Factor Characteristicsmentioning
confidence: 99%
“…The efficiency of the marine green economy is an important indicator to measure its sustainable development (Wei et al, 2021;Ye et al, 2021). At present, scholars mainly have used stochastic frontier method (SFA) and data envelopment analysis (DEA) to evaluate marine green economy efficiency and technical efficiency (Wu, 2018;Zheng et al, 2019;Wang et al, 2021a;Chen et al, 2020b;Chi et al, 2022).…”
Section: Introductionmentioning
confidence: 99%